O itinerário místico de Ernesto Cardenal - Teixeira, Faustino (Revista Eclesiástica Brasileira, 2013)
Conhecido na América Latina e no Caribe como um poeta revolucionário, Ernesto Cardenal (1925-) produziu, ao longo de sua vida, obras em prosa e em verso que estão marcadas igualmente por significativa densidade mística. Há que buscar captar ao longo desse singular itinerário os traços dessa presença espiritual que talvez esteja na base da riqueza e expressividade de sua vida e produção teórica. O poeta nicaraguense vem hoje reconhecido por vários autores como um dos mais fecundos e originais poetas do século XX, e revela-se de fundamental importância desocultar as coordenadas contemplativas presentes na sua rica narrativa. Abstract: Known in Latin America and in the Caribbean as a revolutionary poet, Ernesto Cardenal (1925-) produced during his life works in prose and verse that are equally marked by a significant mystical density. It is now essential to try and capture along this singular trajectory the traits of this spiritual presence that most probably is at the base of the richness and expressivity of his life and theoretical production. The Nicaraguan poet is now recognized by various authors as one of the most productive and original poets of the 20th century and it is of paramount importance to unveil the contemplative coordinates present in his rich narrative. Keywords: Latin America. Literature. Mystical. Religion. Cardenal.